Penerapan Prinsip-Prinsip Good Governance pada PT. BPR Kusemas Dana Mandiri - Edelwis, Ni Luh Putu Katrin; Wirajaya, I Gde Ary (E-Jurnal Akuntansi, 2022)
Since April 2020 PT. BPR Kusemas Dana Mandiri experienced a decline in profit due to the COVID-19 pandemic, but PT. BPR Kusemas Dana Mandiri continues to carry out its operations well and continues to provide full salaries without termination of employment. This study aims to determine the principles of Good Governance (GG) applied to PT. BPR Kusemas Dana Mandiri uses a qualitative method. The data analysis used is descriptive analysis with a qualitative approach. The results of this study state that the principles of transparency, accountability, responsibility, independence and equality and fairness have been implemented properly by PT. BPR Kusemas Mandiri Fund. The implications of this research are expected to be a reminder and evaluation material regarding the importance of applying the principles of Good Governance (GG) in the company's operations. Keywords : Good Governance; Accountability; Transparency; Responsibility.